The prognostic effect of PNN in digestive tract cancers and its correlation with the tumor immune landscape in colon adenocarcinoma. Issue 4 (8th March 2022) - Zhang, Hui; Jin, Ming; Ye, Meng; Bei, Yanping; Yang, Shaohui; Liu, Kaitai
Abstract: Background: The present study investigated the expression, mutation, and methylation profile of PNN and its prognostic value in digestive tract cancers. The disparities in signaling pathways and the immune landscape in colon adenocarcinoma (COAD) based on PNN expression were specifically explored. Methods: The expression, mutation, methylation levels of PNN, and survival data in esophageal cancer, gastric adenocarcinoma, COAD, and rectal adenocarcinoma were evaluated using several bioinformatic databases. Gene Ontology (GO) enrichment analysis and gene set enrichment analysis (GSEA) were performed to investigate the enriched biological functions and pathways in COAD. Several acknowledged bioinformatic algorithms were employed to assess the correlation between PNN expression and the tumor immune landscape in COAD. Results: PNN was upregulated and remarkably related to tumor stage in digestive tract cancers. High expression of PNN was positively associated with poor progression‐free survival and overall survival time, specifically in COAD. PNN expression was identified as an independent prognostic factor in COAD. GO and GSEA analyses revealed that PNN participates in multiple biological processes underlying carcinogenicity in COAD. Further investigation showed that PNN expression was significantly associated with tumor‐infiltrating immune cells, immune cell functions, and several immune checkpoints in COAD. The PNN low expression group had a lower tumor immune dysfunction and exclusion (TIDE) score and a higher immunophenoscore (IPS), indicating a better response to immunotherapy. Conclusion: PNN was highly expressed in digestive tract cancers and could act as an independent prognostic factor and a response predictor for immunotherapy in COAD. Abstract : We downloaded the PNN mRNA expression in digestive tract cancers from TCGA database. PNN was upregulated and remarkably related to tumor stage in esophageal cancer, gastric adenocarcinoma, COAD and rectal adenocarcinoma. PNN expression was identified as an independent prognostic factor in COAD, high expression of PNN was positively associated with poor progression‐free survival and overall survival time, the predictive value for survival was validated in two GEO datasets, GSE17536 and GSE29623. A prognostic nomogram was established for better prognosis prediction in patients with COAD. Furthermore, GO and KEGG enrichment analysis were performed to investigate the enriched biological functions and pathways in COAD. Also, several acknowledged bioinformatic algorithms were employed to assess the correlation between PNN expression and the tumor immune landscape in COAD. PNN expression was significantly associated with tumor infiltrating immune cells, immune cell functions, and several immune checkpoints in COAD.